Financial revolution and economic modernization in Sweden - Anders Ögren (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
The development of a well adapted financial system was a main part of the successful Swedish economic modernization in the latter half of the nineteenth century. In this paper it is shown that this development followed the pattern of a financial revolution. Major institutional and organizational changes that took place roughly between the late 1850s and early 1870s led to a rapid increase in liquidity and financial services. This financial revolution preceded the acceleration in economic growth in general and in the modern, industrial sector in particular. Especially the monetization encouraged growth, both in the industrial sector and in GDP as a whole. The basis of the financial system, measured as commercial bank assets and equity capital, was on the other hand also a result of GDP growth.
Keywords: E44; N13; N23; O16; 330; Financial Development; Growth; Institutions; Liquidity; Monetization; Nineteenth Century; Silver and Gold Standards; Structural Change; Finanzsektor; Finanzinnovation; Wirtschaftswachstum; Industrielle Produktion; Schweden; Wirtschaftsgeschichte